2014
DOI: 10.1088/0957-0233/25/12/125001
|View full text |Cite
|
Sign up to set email alerts
|

Frequency domain analysis of knock images

Abstract: High speed imaging-based knock analysis has mainly focused on time domain information, e.g. the spark triggered flame speed, the time when end gas auto-ignition occurs and the end gas flame speed after auto-ignition. This study presents a frequency domain analysis on the knock images recorded using a high speed camera with direct photography in a rapid compression machine (RCM). To clearly visualize the pressure wave oscillation in the combustion chamber, the images were high-pass-filtered to extract the lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…They found that the knock intensity, represented by the total acoustic energy, was inversely dependent on the extent that flame propagation had been completed before the onset of end-gas autoignition. Furthermore, most of the energy was contained within the first tangential mode, corresponding to knock typically seen in IC engines[323].Qi et al[187] also studied the evolution of gas dynamics under forced ignition conditions within an optically accessible RCM. They utilized a commercial spark plug located in the wall of the reaction chamber with stoichiometric mixtures of iso-octane/air where the geometric compression ratio of the machine was set to 11.35.…”
mentioning
confidence: 99%
“…They found that the knock intensity, represented by the total acoustic energy, was inversely dependent on the extent that flame propagation had been completed before the onset of end-gas autoignition. Furthermore, most of the energy was contained within the first tangential mode, corresponding to knock typically seen in IC engines[323].Qi et al[187] also studied the evolution of gas dynamics under forced ignition conditions within an optically accessible RCM. They utilized a commercial spark plug located in the wall of the reaction chamber with stoichiometric mixtures of iso-octane/air where the geometric compression ratio of the machine was set to 11.35.…”
mentioning
confidence: 99%
“…The STFT could be used to analyze the resonance intensity by integration of the frequency spectrum in the range of the mode under analysis. 31 The first resonance frequency mode (1,0), contains most of the oscillating pressure energy, 32 and is damped in a slower way due to the more intense attenuation of higher frequency modes. 33 The integration of the pressure oscillation energy over the entire frequency domain of 5–15 kHz would be sufficient for analyzing such mode.…”
Section: Resonance Characterizationmentioning
confidence: 99%